Needs Assessment for Interprofessional Education: Implications for Integration and Readiness for Practice - Almalki, Abdulraheem (Healthcare (Basel), 2021)
Interprofessional education (IPE) is an important concept to promote health professionals for interprofessional collaboration. Successful implementation of IPE in health education programs requires consideration of readiness and effectiveness and faces some challenges/barriers. The aim of this study was to examine the perception, understanding and attitude of health profession students and faculty members toward IPE. A cross-sectional study was conducted with students and faculty members from six health professions at Taif University. The study involved administration of the Readiness for Inter-Professional Learning Scale (RIPLS) questionnaire to all students. In addition, focus groups were conducted separately with both students and faculty members. The study showed that only 10 participants (four students, six faculty members) indicated their previous knowledge of IPE. IPE remains a new approach for the majority of students and faculty members. There was no significant difference in the readiness of IPE between professions. Students and faculty members showed positive attitudes toward the IPE curriculum and they believe that it will improve medical education at our university.